The Senologic International Society Survey on Ductal Carcinoma In Situ: Present and Future - Mathelin, C (2022)
Objective: Therapeutic management of ductal carcinoma in situ (DCIS) is heterogeneous among countries worldwide, and some treatment indications are still controversial. To investigate DCIS management in different countries